Forced mobility in Roman legal institutions: the case of “exile” as a political penalty - Souza, Murilo Moreira de (Romanitas - Revista de Estudos Grecolatinos, 2022)
Book review of: FRIGHETTO, R. Exílio e exclusão política no Mundo Antigo: de Roma ao Reino Godo de Tolosa (séc. II a. C. – VI d. C.). Jundiaí: Paco, 2019. 152 p.
Keywords: Mobility; Exile; Politcs; Ancient World